Taxonomic revision of four species of the Neotropical land planarian genera Cratera and Geoplana (Platyhelminthes, Tricladida) with a description of two new species and an emendation of Cratera - Lago-Barcia, Domingo; Carbayo, Fernando (Zootaxa, 2018)
The Brazilian land planarians Cratera crioula, C. joia, Geoplana hina, and G. taxiarcha (Platyhelminthes, Tricladida, Geoplanidae) are revised taxonomically from type material and additional specimens. Geoplana hina sensu Carbayo et al. (2013) was found to be an undescribed species and therefore is described and named as Cratera picuia sp. n. A new species of the genus is also described and named as Cratera arucuia sp. n. G. hina and G. taxiarcha are transferred to Cratera. The most remarkable morphological feature of Cratera—a dilated terminal portion of the ejaculatory duct—is either absent, inconspicuous, or variable in C. hina, C. joia, C. picuia sp. n., and C. arucuia sp. n. Based on the monophyletic status of Cratera inferred elsewhere, an emendation of the genus is here proposed to encompass the morphological variation observed in the genus.